ZBTB32 performs crosstalk with the glucocorticoid receptor and is crucial in glucocorticoid responses to starvation - Lise Van Wyngene (iScience, 2021)
Summary: The hypothalamic-pituitary-adrenal (HPA) axis forms a complex neuroendocrine system that regulates the body’s response to stress such as starvation. In contrast with the glucocorticoid receptor (GR), Zinc finger and BTB domain containing 32 (ZBTB32) is a transcription factor with poorly described functional relevance in physiology. This study shows that ZBTB32 is essential for the production of glucocorticoids (GCs) in response to starvation, since ZBTB32−/− mice fail to increase their GC production in the absence of nutrients. In terms of mechanism, GR-mediated upregulation of adrenal Scarb1 gene expression was absent in ZBTB32−/− mice, implicating defective cholesterol import as the cause of the poor GC synthesis. These lower GC levels are further associated with aberrations in the metabolic adaptation to starvation, which could explain the progressive weight gain of ZBTB32−/− mice. In conclusion, ZBTB32 performs a crosstalk with the GR in the metabolic adaptation to starvation via regulation of adrenal GC production.